Applied ultrasound assisted research on synthesis and in-situ hydrolysis of ammonia borane for hydrogen energy - Filiz, Bilge Coskuner; Figen, Aysel Kanturk; Piskin, Sabriye (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Ultrasound-assisted research on both synthesis and in-situ hydrolysis of ammonia borane (NH3BH3) for hydrogen energy application was experimentally investigated in this study. The salt metathesis reaction between sodium borohydride (NaBH4) and ammonia sulfate ((NH4)(2)SO4) in the presence of organic solvent, tetrahydrofuran (THF), was performed to NH3BH3 synthesis by application of ultrasound. Specifically, the effect of molar ratio (0.96 - 1.06), solvent volume (100-300 ml), time (40-160 min) and temperature (20-60 degrees C) on yield was evaluated to optimize the reaction conditions. The effect of drying process was also assessed under specified conditions, and chemical structures of synthesized samples were compared with commercial supplied NH3BH3. The present investigation provided data on the crystal, and chemical properties of lab-made NH3BH3 and results confirmed the promoting effect of ultrasound on synthesis with excellent yield-96 wt. %. Moreover this, hydrogen deposition characteristits of concentrated lab-made NH3BH3 solutions (5 - 25 wt.%) were assisted by ultrasound to evaluate hydrogen by in-situ reaction in the presence of active metals (Co2+, Ni2+, and Cu2+-). (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Storage; Delivery; Ammonia borane; Ultrasound; In-situ hydrolysis; LARGE-SCALE; DIBORANE; NH3BH3; Chemistry; Electrochemistry; Energy & Fuels